(untitled) (ENTHYMEMA, 2023)
My article compares two sci-fi works: Primo Levi’s short stories “L’ordine a buon mercato” and “Alcune applicazioni del Mimete” – collected in Storie Naturali (1966) – and the film Moon (2009) by the British director Duncan Jones. These two science fiction scenarios, though different in style and narrative plot, are remarkably similar in depicting the enslavement and instrumentalization of human beings, reduced to duplicable, usable and replaceable products in the contemporary machine age. Levi’s literary writing and Jones’ film suggest an ethical-political reflection on both the responsibilities of techno-science and the consequences of the technological process. This article highlights the similar engagement of these two “scenarios of human duplication” in examining the unpredictable ridge of cloning, in which the dialectic between identity and difference produces a dramatic turn that originates in a certain hybris (transgression) of repetition.